The Effect of Social Media Influencer on Purchase Intention with Brand Image and Customer Engagement as Intervening Variables - Ellyne Annida Pramesti; Nurafni Rubiyanti (Journal of International Conference Proceedings, 2023)
An individual with a strong presence on social media, known as an influencer, has the ability to bridge the gap between a company and its target audience by conveying a favorable brand image to the audience. Social media influencers have the ability to shape brand image and customer engagement, which can then influence the interest in purchasing that brand. Tasya Farasya is a beauty influencer who often shares reviews about Makeover products. Her posts have created brand image and customer engagement among Makeover's audience. Compared to other beauty influencers, Tasya Farasya is one of the top 10 beauty influencers in Indonesia, with a high figur of followers and engagement rates. However, the Makeover product that Tasya Farasya reviewed is not the top cosmetic product in Indonesia. This can affect the brand image, customer engagement, and interest in purchasing Makeover.Â This study aims to assess how Tasya Farasya, a social media influencer, affects consumers' purchase intent for Makeover brand, focusing on the influence of brand image and customer engagement factors. In this study, a quantitative approach was employed, whereby data was gathered via a questionnaire. To analyze the data, Structural Equation Model (SEM) was utilized through the use of the SmartPLS software.